Comparative effects of six probiotic strains on immune function in vitro - Dong, Honglin; Rowland, Ian; Yaqoob, Parveen (British journal of nutrition, 2012)
There is considerable interest in the strain specificity of immune modulation by probiotics. The present study compared the immunomodulatory properties of six probiotic strains of different species and two genera in a human peripheral blood mononuclear cell (PBMC) model in vitro. Live cells of lactobacilli (Lactobacillus casei Shirota, L. rhamnosus GG, L. plantarum NCIMB 8826 and L. reuteri NCIMB 11951) and bifidobacteria (Bifidobacterium longum SP 07/3 and B. bifidum MF 20/5) were individually incubated with PBMC from seven healthy subjects for 24 h. Probiotic strains increased the proportion of CD69+ on lymphocytes, T cells, T cell subsets and natural killer (NK) cells, and increased the proportion of CD25+, mainly on lymphocytes and NK cells. The effects on activation marker expression did not appear to be strain specific. NK cell activity was significantly increased by all six strains, without any significant difference between strains. Probiotic strains increased production of IL-1β, IL-6, IL-10, TNF-α, granulocyte-macrophage colony-stimulating factor and macrophage inflammatory protein 1α to different extents, but had no effect on the production of IL-2, IL-4, IL-5 or TNF-β. The cytokines that showed strain-specific modulation included IL-10, interferon-γ, TNF-α, IL-12p70, IL-6 and monocyte chemotactic protein-1. The Lactobacillus strains tended to promote T helper 1 cytokines, whereas bifidobacterial strains tended to produce a more anti-inflammatory profile. The results suggest that there was limited evidence of strain-specific effects of probiotics with respect to T cell and NK cell activation or NK cell activity, whereas production of some cytokines was differentially influenced by probiotic strains.